Electric-dipole spin resonance in wurtzite ZnO - Michaluk, Estera; Wilamowski, Zbysław; Błoniarz, Jacek; Mycielski, Andrzej (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
The electron spin resonance (ESR) measurements of the electric-dipole spin resonance (EDSR) of donor-bound electrons in ZnO wurtzite crystals are reported. This phenomenon was measured in longitudinal Voigt geometry (E1 | | B0 ^ c) at low magnetic field and at low microwave frequency. The ESR transitions observed consist of two comparable signals: magnetic dipole spin resonance (MDSR) and electric dipole spin resonance (EDSR).
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 291-296
Keywords: optyka; semiconductors; spin-orbit coupling; Zeeman and Stark splitting; Jahn–Teller effect; electron paramagnetic resonance and relaxation